Organizational Commitment in Islamic Banking: Does Internal CSR Matter? - Faliza, Nur; Yana, Syaifuddin; Qamarius, Ibrahim; Matriadi, Faisal (Journal of International Conference Proceedings, 2023)
The purpose of this study is to examine the effects on affective organizational commitment of the work environment, skill development, and empowerment as elements of internal corporate social responsibility (ICSR). PLS-SEM or SEM based on variance were utilized to analyze 300 surveys. The study found that organizational commitment is impacted by work environment, skill development, and empowerment in internal CSR. These findings imply that internal CSR, which encompasses skill development, empowerment, and work environment, is a critical component in strengthening organizational commitment to Islamic banking in Aceh. This is the first study to examine the relationship between internal corporate social responsibility and affective organizational commitment in Islamic banking.